Comparison of tension free Desarda technique with Lichtenstein for inguinal hernia repair - Gupta, Abhishek; Sharma, Subash Chandra; Sharma, Janmejai Prasad; Singhal, Pradeep (International Surgery Journal, 2019)
Background: Inguinal hernia is common surgical problem for which mesh based technique, particularly Lichtenstein repair is considered gold standard. However it has its own limitation such as foreign body sensation, wound infection, cord fibrosis, chronic pain, etc. Desarda technique for hernia repair is emerging technique for inguinal hernia repair known for its low cost procedure, less recurrence rate and feasibility of the procedure. The objective of the study was to compare treatment of primary inguinal hernia repair with these methods in terms of various operative and post-operative parameters. Methods: 64 patients included in the study and operated after randomization. Intra-operative time, local complication, return to everyday activity, post-operative pain, foreign body sensation and early recurrence were analysed. Results: 51 patients were analysed with a minimum follow up period of 3 months and rest were lost on follow up. Operative time was less in Desarda’s repair (28.24 vs. 30.88 min). Desarda repair was cost effective, return to everyday activity was early in Desarda group, there was significantly (p<0.001) less post-operative pain measured on VAS on 2nd POD, 7th POD and 1 month. No recurrence observed. Conclusions: Desarda repair is easy to perform and takes less time to perform, it is also cost effective. Desarda repair when compared with Lichtenstein was superior in terms of postoperative pain, return to everyday activity and no foreign body sensation. Desarda repair is superior to mesh based technique in terms of outcome.